(3EMdGd GdYeGdI GdhWfjI eMd GdYeGdI GdhGaOI aj GdeedcI GdYQHjI GdSYhOjI (B/ s - (3YHOGddg Ydj ESeGYjd HOjhjs; (3CMeO MSf GdHQYj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2021)
(3ehVhY GdHMK h gh EMdGd GdYeGdI GdhWfjI eMd GdYeGdI GdhGaOI ai GdeedcI GdYQHjI GdSYhOjI(B: (3jYJHQ ef GdehVhYGJ PGJ GdUdI HMeGjI Mbhb GdYeGdI GdCLfHjI HeNJda Ohd GdYGde(B: (3jYJHQ ef GdehVhYGJ PGJ GdUdI HMeGjI Mbhb GdYeGdI GdCLfHjI HeNJda Ohd GdYGde(B: (3HeG ajgG GdeedcI GdYQHjI GdSYhOjI(B: (3h bO Je eYGdLJg ai ebOeI JHjf ehVhY h CgejJgG(B: (3h efgLjJgG h HGH JegjOi HYfhGf XGgQI GdYeGdI GdhGaOI ai GdeedcI GdYQHjI GdSYhOjI(B: (3h HGH Chd HYfhGf(B: (3eaghe GdEMdGd h eYhbGJg(B: (3h HGH KGfi(B:(3HYfhGf(B: (3XGgQI GdYeGdI GdhGaOI h SjGSI GdeedcI fMh GdEMdGd h GdSYhOI(B: (3h bO JVef GdHMK NGJeI JHjf Cge GdfJGFL h GdJhUjGJs
The topic of the research, which is the substitution of national labor for expatriate labor in the Kingdom of Saudi Arabia, is considered one of the topics related to the protection of the rights of foreign labor in various countries of the world. An introduction showing the subject, its importance, its methodology and an introductory chapter entitled the phenomenon of expatriate workers in the Kingdom of Saudi Arabia, and a first chapter entitled: The concept of replacement and its obstacles, and a second chapter, entitled: The phenomenon of expatriate workers and the Kingdom's policy towards replacement and Saudization, and the research included a conclusion showing the most important results and recommendations.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2021.s
(3HHdjhLQGajG(B: (3UaMGJ(B214-225.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdYeGdI GdhWfjI s; (3GdYeGdI GdhGaOI s; (3GdYeGdI GdCLfHjI s; (3GdMbhb GdTNUjI ddYGed GdegGLQ s; (3Mbhb GdYGed GdegGLQ s; (3GdeSGhGI aj GdCLQ eY GdhWfjjfs; (3Mbhb GdYGed GdegGLQ aj GdJCejfGJ GdGLJeGYjI s; (3GdTQhW GdELQGFjI dJTZjd GdCLGfH s; (3fXGe GdYed GdSYhOj s; (3Mbhb GdYGed GdCLfHj s; (3JhWjf GdhXGFa s; (3Shb GdYed GdSYhOj s; (3GdHWGdI s; (3GdYeGdI GdhWfjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2021